Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran TGT Dalam Pembelajaran Matematika Kelas 2 SDN 1 Karangduren Tahun Ajaran 2023/2024 - Agatha Erika Citra Nilasari; Putri Zudhah Ferryka; Yuliana Yuliana (CV. Alim's Publishing, 2024)
The background to this research is the low student learning outcomes which are less than the KKTP, namely 75. Many students are busy alone and do not pay attention to the teacher and the learning model is less interesting. The teacher uses a lecture learning model and uses an LCD to play guessing games. The aim of this research is to improve the learning outcomes of grade 2 students at SD N 1 Karangduren by using the TGT (Team Games Tournament) learning model. This research is classroom action research which lasts for two cycles consisting of planning, action implementation, observation and reflection stages. The research subjects were 2nd grade students SD N 1 Karangduren. The data collection technique in this research is pre-test and post-test questions which consist of multiple choice, matching, true-false and description questions. Based on the research results obtained on Building Space material, it can be improved by using the TGT (Team Games Tournament) learning model. The incrase in learning outcomes can be seen from the initial condition, the average value is 29%. In cycle I there was an incrase with an average of 47%. The in cycle II there was an incrase with an average og 88%.